Community Participation Study in Sanitation Program (Case Study: Panton Labu Village, North Aceh) - Nurhayati S (Jurnal Teknologi Terapan and Sains 4.0, 2021)
Health is the standard of welfare in a country, one of them influenced by sanitation facilities owned by the environment settlement. The behavior of some people who still pay less attention to sanitation problems is the reason for a disease to spread. To overcome the problem of the environmental health quality the Indonesian government is trying to provide an infrastructure that can stimulate and direct the community to play an active role in the sanitation development through a program called the SANIMAS (Sanitation by the Community), so that ultimately they can manage infrastructure independently. The research was conducted in Pantonlabu Village, Tanah Jambo Aye District, North Aceh Regency. This research aims to analyze the level of community participation in the SANIMAS program. This study uses a quantitative method by using the Arnstein model of community participation to analyze the collected data. The results indicate that the level of participation provided by the community is increasing gradually. At the planning stage, the level of community participation is at the 4th level, namely consultation, then at the design stage going up at the 5th level namely placation, and at the development stage, there is an increase which is at the 6th level of Arnstein ladder namely partnership. Finally, this research can be useful as a reference for local government in carrying out similar activities in other locations to ensure that programs that require community participation can run and achieve maximum results as expected.Keywords: community, community participation, level of participation, sanitation, SANIMAS